2020
DOI: 10.3390/ijerph17228492
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult Segmentation According to Residentially-Based Lifestyles and Analysis of Their Needs for Smart Home Functions

Abstract: Globally, the percentage of older people in the general population is growing. Smart homes have the potential to help older adults to live independently and healthy, improving their quality of life, and relieving the pressure on the healthcare and social care systems. For that, we need to understand how older adults live and their needs. Thus, this study aims to analyze the residentially-based lifestyles (RBL) of older adults and segment them to compare and analyze the real needs of smart home functions for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…They are published in Environmental Science Ecology (21 publications), Architecture (5 publications), and Art (2 publications); many of them were conducted recently from 2020 to 2022. When looking at some of the studies in these areas, Yu et al (2020) categorized the residential-based lifestyle of older adults and studied each group’s diverse needs for smart home functions [ 2 ]. Kwon et al (2021) investigated the objective diagnosis method of dementia through automatic classification of early-stage dementia based on ADL data obtained in a smart home environment [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They are published in Environmental Science Ecology (21 publications), Architecture (5 publications), and Art (2 publications); many of them were conducted recently from 2020 to 2022. When looking at some of the studies in these areas, Yu et al (2020) categorized the residential-based lifestyle of older adults and studied each group’s diverse needs for smart home functions [ 2 ]. Kwon et al (2021) investigated the objective diagnosis method of dementia through automatic classification of early-stage dementia based on ADL data obtained in a smart home environment [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to focus on the “characteristics of smart home interface design and their impact on people of various ages” [ 83 ]. How people adopt smart home technology is “still an understudied area” [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yu et al surveyed 271 Korean OAs assessing their smart home technology needs. 39 Based on the participant’s interest; they identified five main technology domains; safety (e.g., emergency contact, fall, gas-leak, smoke detection), healthcare-related (e.g., measure sleep and mental health, medication reminder, telehealthcare, wearable sensors), automation (e.g., heating, checked post-box, electricity), entertainment and home assists (e.g., automatic TV play function/personalized content, home assistant Robot). The study identified five clusters with various priorities of technology functions.…”
Section: Future Planningmentioning
confidence: 99%